Reliability of structure under random earthquake motion - Chern, Chuen-hsiung; Takemiya, Hirokazu; ROC Government (Bangkok : Asian Institute of Technology, 1976)
This paper deals with the safety evaluation of a bilinear hystere tic system under first excursion over a specified barrier and low-cycle fatigue process when subjected to random earthquake motion. The first passage approximation is based on the assumption that the passage level is so high that the crossing of barrier may be considered as statically independent, the crossing then becomes a Poisson process. Also the Palmgren and Miner's hypothesis is applied to compute the low-cycle fatigue damage. The reliability associated is evaluated as a function of time. Comparison is made between these two types of failure to investigate the ductility effect. The responses under nonstationary white noise and filtered shot noise are determined for the auxiliary system which is derived through linearization technique. Furthermore, a powerful method to evaluate the covariance matrix of the response is adopted.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Earthquakes and building; Earth movements and building